PREDICTION AND CONTROL OF THINNING RATE OF DEFORMATION ZONE THICKNESS IN METAL SHEET SINGLE POINT INCREMENTAL FORMING PROCESS - FAN Yuan; LI Yan; YANG MingShun; YAO ZiMeng; BAI Lang (Jixie qiangdu)
Excessive thinning rate of deformation zone thickness in metal sheet single point incremental forming process is an important factor that influence the forming limit. Prediction of deformation zone thickness is an important way to control the rate of thinning. The process of deformation zone thickness in single point incremental forming process were analyzed,the finite element model of single point incremental forming was established by the finite element analysis software ABAQUS and the 1060 Aluminum was selected as material of sheet. A relatively high accuracy formula to predict the deformation zone thickness is fitted by using the simulation results. the impact of process parameters such as tool diameter,layer step,feeding speed,sheet thickness,forming angle on thinning rate were analyzed respectively. The correctness of finite element simulation was verified by experiment and proposed a method to control thinning rate by changing forming trajectory. The results showed that the thinness value calculated by fitted formula to predict the deformation zone thickness is more close to the experimental data than by sine theorem. Thinning rate of deformation zone thickness increases with the increase of tool diameter,forming angle and sheet thickness and the decreases of step size,the feeding speed had no significant effect on the thinning rate. The most important factor of thinning rate is forming angle. The thinning rate is effectively reduced by using pressing point uniformly distributed forming trajectory.